Electricity production performance and pH optimization of MFCs using enriched starch-degrading culture - Sheng-chao Gao; Hui-chun Jiang; Zhen Zhang; Xin-xin Fan; Tian-peng Gao; Ying Liu (iScience)
Summary: The untreated wastewater from starch production can damage the balance of the aquatic ecosystems. This study enriched a mixed culture (EHN) with electrochemical activity and starch degradation capabilities. EHN exhibited growth across a pH range of 5.5–9.5, with electricity generation performance investigated at different pH levels. At pH 9.0, the maximum current density was 556.83 μA cm−2, 17.77 and 72.51 times higher than that at pH 7.2 and 5.5, respectively. The maximum power density and voltage at pH 9.0 were 1,499.93 mW m−2 and 631.00 mV, respectively, higher than those at pH 7.2. Bacillus was the dominant genus at pH 9.0. High-performance liquid chromatography (HPLC) revealed faster starch degradation and acetate production at pH 9.0, attributed to enhanced amylase activity, which indirectly boosted EHN’s electricity generation. This work highlights the potential of EHN in wastewater treatment and bioelectricity generation.